2017
DOI: 10.1159/000475977
|View full text |Cite
|
Sign up to set email alerts
|

Triggering of Eryptosis, the Suicidal Erythrocyte Death, by Perifosine

Abstract: Background/Aims: The alkylphospholipid perifosine is used for the treatment of malignancy. The substance is effective by triggering suicidal tumor cell death or apoptosis. Side effects of perifosine include anemia. At least in theory, perifosine-induced anemia could result from stimulation of suicidal erythrocyte death or eryptosis. Hallmarks of eryptosis are cell shrinkage and cell membrane scrambling with phosphatidylserine translocation to the erythrocyte surface. Cellular mechanisms participating in the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 98 publications
0
7
1
Order By: Relevance
“…Though other authors have reported ca . 30% hemolysis after a 24-h exposure to 5.4 μM perifosine (Egler and Lang, 2017 ), a direct correlation with our results was difficult, due to significant differences in the experimental conditions.…”
Section: Resultscontrasting
confidence: 54%
“…Though other authors have reported ca . 30% hemolysis after a 24-h exposure to 5.4 μM perifosine (Egler and Lang, 2017 ), a direct correlation with our results was difficult, due to significant differences in the experimental conditions.…”
Section: Resultscontrasting
confidence: 54%
“…In brief, control and experimental cells were stained with 1% Annexin-V-FITC in 5 mM CaCl 2 buffer (v/v) for 10 min at room temperature away from light, and the percentage of Annexin-positive cells was obtained at 488/520 nm excitation and emission spectra, respectively. FSC, as a reflection of cell size, was simultaneously recorded (Egler & Lang, 2017).…”
Section: Ps Externalization and Forward Scatter (Fsc)mentioning
confidence: 99%
“…A number of chemotherapeutic agents have previously been shown to induce eryptosis (Egler & Lang, 2017;Lang et al, 2006) which may explain the anemia associated with treatment (Lang et al, 2017). pyran-5,6-dione, C 15 H 14 O 3 ; LAP), a naphthoquinone that naturally occurs in extracts of Lapacho tree (Lamberti et al, 2013) (Figure 1a), possesses an antitumor activity in vitro and in vivo (Ferraz da Costa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…During the process of anemia, the membrane of erythrocyte was injured, resulting in erythrocyte apoptosis. So far, more and more evidence has shown that organisms could initiate erythrocyte apoptosis to maintain homeostasis of anemia patients ( Knapp et al, 2012 ; Egler and Lang, 2017 ). Our research group have confirmed that herb pair Danggui-Chuanxiong could suppress erythrocyte apoptosis by inhibiting sphingolipids dependent signaling molecules ( Li W.X.…”
Section: Discussionmentioning
confidence: 99%